2020
DOI: 10.1111/ssqu.12788
|View full text |Cite
|
Sign up to set email alerts
|

Knowing What You Don't Know: The Role of Information and Sophistication in Ballot Completion

Abstract: Objective. We seek to examine how individual factors such as information and political sophistication can affect the likelihood of a voter completing his or her ballot. Methods. Through the use of an original experiment, we examine the individual-level effects of information and political sophistication on ballot completion. Results. We find that having less information about the candidates on a ballot results in lower levels of ballot completion. On average, voters complete 19 percent less of their ballot whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Debate exists regarding the causal mechanisms, but it has long been observed that voters with higher levels of education and income are generally more likely to turn out (Mayer, 2011, Franko et al, 2016), complete ballots (Lamb and Perry, 2020), and be more politically engaged (Sunshine Hillygus, 2005). Differences in education and income also influence familiarity with voting and changing electoral systems (Burden, 2009; Sondheimer et al, 2010; Tenn, 2007), which could contribute to a higher likelihood of ballot voiding errors among voters in lower education and lower income areas.…”
Section: Expectationsmentioning
confidence: 99%
“…Debate exists regarding the causal mechanisms, but it has long been observed that voters with higher levels of education and income are generally more likely to turn out (Mayer, 2011, Franko et al, 2016), complete ballots (Lamb and Perry, 2020), and be more politically engaged (Sunshine Hillygus, 2005). Differences in education and income also influence familiarity with voting and changing electoral systems (Burden, 2009; Sondheimer et al, 2010; Tenn, 2007), which could contribute to a higher likelihood of ballot voiding errors among voters in lower education and lower income areas.…”
Section: Expectationsmentioning
confidence: 99%